Unidades de ensino potencialmente significativas: uma contribuição à formação inicial de licenciandos em química - Moreira, Eliani Jordana da Silva (2019)
The effective improvement of the teaching-learning process occurs through the intervention of the teacher and the continuous improvement on his pedagogical practice in initial and continuing education actions. Thus, the school is an environment conducive to research and investigation of the potential of different methodologies. In this sense, Potentially Meaningful Teaching Unit (PMTU) - , theoretically based teaching sequences - are focused on Significant Learning, since they can stimulate applied research in teaching, that focus directly to the classroom. Science teaching sequences emerge as an attempt to bring the context of scientific knowledge into practice in the classroom. Therefore, the present work investigated to what extent a structured didactic intervention in PMTU can be seen by chemistry graduates as viable and interesting to work with chemical contents. To that end, we applied a workshop entitled "Potentially Meaningful Teaching Unit: A Contribution to the Initial Training of IFRN Chemistry Teachers, Apodi Campus", based on David Ausubel's Theory of Significant Learning (TAS). The workshop was held with students of the Licentiate course in Chemistry of the IFRN, Apodi campus. We adopted quantitative research, using the Likert scale and qualitative, based on active research, in the form of action research. The quantitative data were treated according to the classical statistics, using the arithmetic mean and standard deviation as measures of centrality. As for the qualitative data, they were constructed from the Bardin Content Analysis. The analysis of the post-workshop data indicated that the students perceived the PSTU as interesting to be used in their classes, however, considered to be of little viability due to time-related aspects of their preparation and also to develop a practice still linked to traditional teaching , in which the teacher is regarded as the holder of knowledge. With this work we can also see the importance of spaces in the initial formation of teachers that allow the discussion and the development of proposals of teaching with diversified approaches, which can collaborate in a perspective of change in teaching